Fate of N-15 fertilizer applied to maize in rotation with tropical forage grasses - Rocha, Kassiano F. [UNESP]; Mariano, Eduardo [UNESP]; Grassmann, Camila S. [UNESP]; Trivelin, Paulo C. O.; Rosolem, Ciro A. [UNESP] (Elsevier B.V., 2019)
Tropical forage grasses of the genus Megathyrsus and Urochloa can suppress soil-nitrification by releasing inhibitory substances, reducing N losses and increasing fertilizer N recovery of the cash crop in rotation. In contrast, ruzigrass (Urochloa ruziziensis) has been reported to decrease the yield and N accumulation of the subsequent crop and hence can affect N use efficiency and the fate of applied N. We investigated the effects of Guinea grass (M. maximum), palisade grass (U. brizantha), and ruzigrass on succeeding crop yield, N accumulation, and the fate of N-15-labeled fertilizer applied to maize (Zea mays L.) in a 2-year field experiment in Brazil. Maize was fertilized with 140 kg ha(-1) N as ((NH4)-N-15)(2)SO4 or not fertilized, and recovery of residual N-15 was quantified in the second season. Net nitrification rates through an incubation study had no differences among grasses. Nitrogen application increased maize yield and N accumulation in both seasons, whereas maize yield decreased by 9.5% following ruzigrass compared with the other forages. The grasses had no effect on N-15 recovery by maize or in the system. On average, the recovery of N-15 in maize and soil was 34% and 46% in the first growing season and 2.9% and 20% in the second season, respectively. Our results indicated that tropical perennial grasses had no differential effects on nitrification rates and the fate of N-15-labeled fertilizer in the plant-litter-soil system in the season of application nor in the subsequent crop (residual effect).
Keywords: Zea mays L.; Brachiaria; N-1(5); Nitrogen uptake efficiency; Soil N loss